2021
DOI: 10.3390/ijms22041706
|View full text |Cite
|
Sign up to set email alerts
|

Calprotectin in Lung Diseases

Abstract: Calprotectin (CLP) is a heterodimer formed by two S-100 calcium-binding cytosolic proteins, S100A8 and S100A9. It is a multifunctional protein expressed mainly by neutrophils and released extracellularly by activated or damaged cells mediating a broad range of physiological and pathological responses. It has been more than 20 years since the implication of S100A8/A9 in the inflammatory process was shown; however, the evaluation of its role in the pathogenesis of respiratory diseases or its usefulness as a biom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
26
1
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(32 citation statements)
references
References 204 publications
(351 reference statements)
0
26
1
2
Order By: Relevance
“…In this study, they used high-dimensional flow cytometry and single-cell RNA sequencing of COVID-19 peripheral blood and suggested that high calprotectin production is mediated by abnormal myeloid subsets [ 54 ]. Calprotectin genes are also expressed in lungs, particularly in lung epithelial and alveolar type II pneumocytes [ 55 ]. Likewise, the expression of these genes is increased with viral infection [ 56 ] and lipopolysaccharide stimulation [ 57 ].…”
Section: Discussionmentioning
confidence: 99%
“…In this study, they used high-dimensional flow cytometry and single-cell RNA sequencing of COVID-19 peripheral blood and suggested that high calprotectin production is mediated by abnormal myeloid subsets [ 54 ]. Calprotectin genes are also expressed in lungs, particularly in lung epithelial and alveolar type II pneumocytes [ 55 ]. Likewise, the expression of these genes is increased with viral infection [ 56 ] and lipopolysaccharide stimulation [ 57 ].…”
Section: Discussionmentioning
confidence: 99%
“…S100A8 and S100A9 form a heterodimer complex called Calprotectin (CLP). Elevated levels of CLP is found in bronchoalveolar lavage fluid (BALF), serum and lung tissue of pneumonia patients 23 . Serum CLP could be potential biomarker for COVID-19 and further research is required to test this hypothesis 24 .…”
Section: Discussionmentioning
confidence: 99%
“…The upregulation of calprotectin expression has been associated with various inflammatory processes such as inflammatory bowel disease, rheumatoid arthritis, spondyloarthritis and cardiovascular disease in type 2 diabetes mellitus (6)(7)(8)(9). Additionally, calprotectin is crucial for neutrophil accumulation and inflammation in the lung parenchyma during bacterial community acquired pneumonia (10).…”
Section: Discussionmentioning
confidence: 99%